A Tropical Traumaturgy: Rereading the Folk in "May Bagyo Ma't May Rilim" - Benitez, Christian Jil R (Archīum Ateneo, 2022)
As a counterpoint to the foremost understanding of the poem dubbed as “May Bagyo Ma’t May Rilim” (lit. “There may be storm and dark”) (1605) as an articulation of an unnamed native’s submission to Catholicism, as well as a testament to their then unwavering faith, the present essay attempts to reconsider the poem through a comparative reading alongside folk poetry wagered to have come from earlier times. In other words, the poem is reread through a temporal realignment of it in the conventional periodization of Philippine (literary) history, moving it from its frequent grouping among texts from (early) Spanish colonization and toward an assemblage with the so-called precolonial texts, such as the folk bugtong (riddle), salawikain (proverb), dalit (octosyllabic quatrain), and hudhud (an Ifugao epic). In reinscribing the poem with these texts, the aforementioned understanding of the poem as merely an affirmation of Catholic faith is then eluded, allowing instead the emergence of a certain folk traumaturgy, that is, a trauma-work that recognizes súgat as a wound whose arrival is most accepted and anticipated, if only to transfigure it as well as an opportunity. This traumaturgy intuited from the poem is therefore perceived to be an embodiment of tropicality, not on its reliance on the “precolonial” folk sensibility that is yet to be tempered or colonized, but in its demonstration of a turn that poetically attenuates terror and transforms it as a moment perhaps of the erotic.